Prophetic Parenting in Digital Age - Nanang Abdillah (Journal of Social Science and Economics, 2022)
The first education given by parents will greatly underlie a person's personality. Rasulullah SAW. said, "Every child is born in a state of fitrah. Then the two parents who will become the child will become a Jew, Christian, or Magian as cattle that give birth to livestock perfectly. In relation to children's education, the digital era actually offers a variety of convenience opportunities, however, the magnitude of the threat cannot be underestimated. The development of technology that is increasingly sophisticated with the number of social media circulating, does not rule out the possibility that children will be carried away with the negative impacts of technology if they are not provided with sufficient moral education. The more sophisticated the technology, the easier it is to access various information. This ease of access will have a positive or negative impact. The thing that becomes a big homework for parents is to prepare their children to face their era. Facing the challenges of this digital era, parents must equip their children with strong moral and creed education in order to form an Islamic personality by referring to the upbringing of the Prophet SAW.